Mandibular and Dental Manifestations of Gaucher Disease - Saranjam, Hamid R. (2012)
Gaucher disease is a systemic lysosomal storage disorder with a high prevalence among Ashkenazi Jews. It is caused by an inherited deficiency of the lysosomal enzyme glucocerebrosidase. Common signs and symptoms include hepatosplenomegaly, anemia, thrombocytopenia, and skeletal involvement. Oral and dental manifestations are less commonly seen. These manifestations are often asymptomatic, although they may be detected by routine dental x-rays. There are several case reports and a few larger series published describing patients with Gaucher disease who have mandibulo-maxillofacial involvement. This review aims to examine the oral manifestations observed in Gaucher disease and to suggest practical guidelines for dealing with these often worrisome signs. Among the critical issues are the benign nature of Gaucher cell infiltration of the mandible and the critical importance of being prepared for post-procedure bleeding and/or infections. Therefore, it is essential that dental practitioners be aware of the possible oral and dental complications of Gaucher disease, as well as the available treatment modalities.